2010
DOI: 10.1007/s00259-009-1362-z
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal response to mental stress in patients with Takotsubo cardiomyopathy detected by gated single photon emission computed tomography

Abstract: Mental stress may evoke regional and/or global abnormalities in most TTC patients. The abnormal response to mental stress supports the role of sympathetic stimulation in TTC. Mental stress could thus be helpful for TTC evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
2
0
2
Order By: Relevance
“…Respecto a una eventual persistencia de las alteraciones segmentarias, en relación a disturbios de catecolaminas, existe evidencia de alteración apical precoz y hasta 6 meses mediante imágenes con metayodobenzilguanidina marcada 19 . En pacientes con STT sometidos a estrés mental, al menos 1 mes post inicio del cuadro, se demostró dilatación post-estrés y alteraciones de motilidad segmentaria transitoria en la mayoría de los casos con STT respecto a grupo control, sin alteraciones coronarias 20 .…”
Section: Discussionunclassified
“…Respecto a una eventual persistencia de las alteraciones segmentarias, en relación a disturbios de catecolaminas, existe evidencia de alteración apical precoz y hasta 6 meses mediante imágenes con metayodobenzilguanidina marcada 19 . En pacientes con STT sometidos a estrés mental, al menos 1 mes post inicio del cuadro, se demostró dilatación post-estrés y alteraciones de motilidad segmentaria transitoria en la mayoría de los casos con STT respecto a grupo control, sin alteraciones coronarias 20 .…”
Section: Discussionunclassified
“…Neuroimaging studies have shown that patients with TTS have structural alterations in the limbic system and reduced functional connectivity among brain regions of the cortico-limbic network, comprising the prefrontal cortex, right insula, amygdala, hypothalamus, cingulate cortex, and thalamus, all of which regulate the autonomic nervous system and the CV response to mental stress [ 137 , 138 , 139 , 140 , 141 ]. The altered functional connectivity pattern may persist for weeks following the acute cardiac event, well after the recovery of left ventricular dysfunction [ 142 ]. Reduced functional brain connectivity may precede the development of TTS by years.…”
Section: Clinical Conditions Associated With Mental Stressmentioning
confidence: 99%
“…Как известно, у пациентов с депрессивными расстройствами наблюдается нарушение обратного захвата нейронами норэпинефрина из синаптической щели [14,17]. Это, в свою очередь, способствует длительной стимуляции симпатической нервной системы (СНС) и при возникновении стрессорной ситуации может приводить к сократительной дисфункции ЛЖ [18].…”
Section: роль центральной нервной системы в патогенезе заболеванияunclassified